Influence of Platen Temperatures and Storage Conditions on the Survival of Freeze-dried Salmonella typhimurium - Sinskey, T. J. (1967)
Salmonella typhimurium survived freeze-drying at a platen temperature of 120 F (48.9 C) and also, though to a much lesser degree, at 160 F (82.6 C). The extent of the survival at these temperatures was dependent on the composition of the model system employed. The incidence of damage immediately after freeze-drying was greater for cells dried at the higher platen temperature and was influenced by the composition of the menstruum in which the cells were dried. In model systems having protein-dominant isotherms, survival during subsequent storage depended greatly on relative humidity, with recovery highest at relative humidities below those corresponding to moisture contents at which a monomolecular layer is formed. In menstrua having a higher sugar content, survival was best at low relative humidities corresponding to a very low equilibrium moisture content in the model system used. Damage during storage tended to be a function of the composition of the gels in which the organisms were freeze-dried, and also depended greatly on the presence of air and on the relative humidity. The maximal percentage of damage usually occurred at the low relative humidities as storage time increased.